Pengaruh Terpaan “Desak Anies”, Political Branding dan Kredibilitas Anies Terhadap Minat Memilih Warga Jakarta - Ariefin, Choyrull; Herna (Kinesik, 2024)
This study aims to analyze the influence of exposure to the YouTube show "Desak Anies", political branding, and the credibility of Anies Baswedan on the interest in voting for DKI Jakarta residents. The results of the study show that the variables of exposure to impressions, political branding, and the credibility of Anies Baswedan, significantly affect the interest in voting for DKI Jakarta residents. In the political branding variable, the "positioning" indicator shows the public's interest in Anies' distinctive personal branding which in the "Desak Anies" program creates direct interaction. The highest indicator of the credibility variable "attractiveness" shows that Anies has a high personal appeal in increasing people's interest in voting. The results of the study emphasize the importance of appropriate communication programs in political campaigns to build voter interest.